ЗМІНИ ПОЛЯРИЗАЦІЇ МАКРОФАГІВ У ДИНАМІЦІ РОСТУ МЕТАСТАЗУЮЧОЇ КАРЦИНОМИ ЛЬЮЇС - Chumak, A.V.; Fedosova, N.I.; Cheremshenko, N.L.; Symchych, T.V.; Voyeykova, I.M.; Chekhun, V.F. (PH Akademperiodyka, 2023)
Aim: To assess the functional state of macrophages based on various manifestations of their activity at the different stages of metastatic tumor growth in C57Bl mice. Materials and Methods: On days 7, 14, 21 and 28 after Lewis lung carcinoma transplantation to C57Bl mice, macrophages from various anatomic sites were isolated and tested on their cytotoxicity, metabolic activity, NO production and arginase activity. Results: In the populations of peritoneal and splenic macrophages, on days 7 and 21 of tumor growth antitumor (M1) cells prevailed while on days 14 and 28 tumor-promoting (M2) macrophages predominated. In the population of lung macrophages, cells with M1 phenotype were in the majority in the early stages of tumor growth. On days 21 and 28, M1 cells were gradually substituted by cells exhibiting M2 phenotype. This shift correlated with metastasis to lungs. Conclusion: Lewis lung carcinoma growth is accompanied by the gradual change in macrophage polarization from antitumor (M1) towards tumor-promoting (M2) type. These changes were more evident in population of lung macrophages and correlated with the parameters of metastasis.